Knowledge and Attitudes of Non-Medical Faculty Students Batch 2020 about Polycystic Ovarian Syndrom (PCOS) at Tarumanagara University - Maria Edelin Fortuna; Julia Herdiman (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Polycystic Ovarian Syndrome (PCOS) is one of the most common hormonal disorders in women of childbearing age (WUS). Signs and symptoms experienced by PCOS patients are obesity, menstrual cycle ≤ 21 days or ≤ 35 days, hirsutism, excessive acne, acanthosis nigricans, skin tags, and alopecia. This study aims to determine the knowledge and attitudes in the Faculty of Non-medical students at Tarumanagara University related to PCOS.This research is a qualitative research with descriptive research design conducted at Tarumanagara University. Samples were taken between January and May 2022 among Non-medical Faculty Students batch 2020. Questionnaires were filled out and analyzed using a computer device. The knowledge levels of Non-medical Students at Tarumanagara University are categorized as" Good "47%," Sufficient "42 %, and" Bad" 11%. The categories of attitudes obtained 95% as “Good” and 5% as “Sufficient”. Those suspected of suffering PCOS as many as 17%, while the rest did not seem to suffer PCOS. Level of knowledge and attitude of Non-medical Faculty Students on PCOS is mostly “good" category. Only 17% were suspected of suffering PCOS. Keywords: Attitude, Knowledge, PCOS